2017
DOI: 10.1002/ijc.30612
|View full text |Cite
|
Sign up to set email alerts
|

The effect of medications which cause inflammation of the gastro‐oesophageal tract on cancer risk: a nested case–control study of routine Scottish data

Abstract: Novelty and Impact: This is the first study to investigate the impact of tetracyclines and spironolactone use on gastro-oesophageal cancer risk. Our findings should provide considerable reassurance to the many GPs and patients prescribing or taking these medications. Previous evidence around the effect of bisphosphonates on gastro-oesophageal cancer risk is mixed. Our work provides further evidence of no association, and could suggest that previous findings of positive associations might have been impaired by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 38 publications
(45 reference statements)
0
12
0
3
Order By: Relevance
“…Die Datenlage hierzu ist widersprüchlich [58 -62]. Nach der jüngsten Fall-Kontroll-Studie fand sich ein geringfügig erhöhtes Risiko für Bisphosphonate (OR 1,34; 95 % CI 1,03 -1,74), ohne dass eine Dosisabhängigkeit festgestellt werden konnte [63].…”
Section: Hintergrundunclassified
“…Die Datenlage hierzu ist widersprüchlich [58 -62]. Nach der jüngsten Fall-Kontroll-Studie fand sich ein geringfügig erhöhtes Risiko für Bisphosphonate (OR 1,34; 95 % CI 1,03 -1,74), ohne dass eine Dosisabhängigkeit festgestellt werden konnte [63].…”
Section: Hintergrundunclassified
“…Characteristics and information of 10 studies are shown in Table 1. In total, there were four cohort studies 15‐18 and six nested case‐control studies 19‐24 incorporated into our analysis. Two of the studies only included women, and the other eight studies included both men and women.…”
Section: Resultsmentioning
confidence: 99%
“…Two of the studies were taken in South Korea, one in Denmark, two in Taiwan, two in England, two in America and one in Scottish. In addition, nine of the studies 15‐23 showed that there was no significant association found between bisphosphonate use, and a little correlation was found in the remaining study 24 . All studies provided an adjusted effect size.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations